The Effect of Social Capital and Learning Organization on Marketing Performance Through the Marketing Strategy - Sholekhah, Ika Maratus; Widodo, Joko; Wahyono, Wahyono (Universitas Negeri Semarang, 2020)
The purpose of this study is to analyze the effect of social capital, leraning organization to marketing performance either directly or indirectly through marketing strategy. The method used in this study is quantitative method and analyzed by path analysis by using SPSS. The object of this study is the soft-boned milkfish entepreneurs in Semarang city and the sample is 64 respondents. The result of research shows that social capital has a significant effect on marketing perfromance of -28.3%; social capital has no effect on marketing stratgey; social capital has no effect on marketing performance through marketing strategy; learning organization has a significant effect on marketing performance of 61.6%; learning organization has a significant effect on marketing strategy of 50%; learning has a significant effect on marketing performance through marketing strategy of 89.9%; and marketing strategy has a significant effect on marketing performance of 56.7%